Direct activation of platelets by addition of CaCl2 leads coagulation of platelet-rich plasma - Toshihisa Toyoda; Kazushige Isobe; Tetsuhiro Tsujino; Yasuo Koyata; Fumitaka Ohyagi; Taisuke Watanabe; Masayuki Nakamura; Yutaka Kitamura; Hajime Okudera; Koh Nakata; Tomoyuki Kawase (SpringerOpen, 2018)
Abstract Background Based on the notion that full activation of platelets is required for a growth factor release, in regenerative dentistry, platelet-rich plasma (PRP) in liquid form is usually clotted by addition of CaCl2 in glassware before topical implantation. However, there has been no evidence as to which is better, full or partial activation of platelets, for minimizing the loss of growth factors and improving the controlled release of growth factors from coagulated PRP. To address this matter, here, we primarily examined direct effects of CaCl2 on platelets in PBS and on coagulation in citrated PRP. Methods PRP was prepared from healthy volunteers' blood. Platelets' actions were monitored by scanning electron microscopy, flow cytometry, digital holographic microscopy, and immunofluorescent staining. Clot formation was examined in plasma. Results In plasma-free PBS, 0.1% CaCl2 immediately upregulated CD62P and CD63, causing a release of microparticles and fibrinogen/fibrin; consequently, platelets aggregated and adhered to polystyrene culture dishes with enlargement of their attachment area. In a clot formation assay in plasma, CaCl2 initially induced platelet aggregation, which triggered loop-like matrix formation and subsequently induced coagulation on a watch glass. Such changes were not clearly observed either with PRP in a plastic dish or in platelet-poor plasma on a watch glass: coagulation was delayed in both conditions. Conclusions These findings indicate that besides the well-known coagulation pathway, which activates platelets via thrombin conversion in a coagulation cascade, CaCl2 directly activates platelets, which then facilitate clot formation independently and in cooperation with the coagulation pathway.